2017
DOI: 10.5546/aap.2017.eng.541
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child discrepancy in the assessment of health- related quality of life using the EQ-5D-Y questionnaire

Abstract: Introduction. The assessment of health-related quality of life (HRQoL) serves to detect changes over time in patients' health status and allows to do a cost-effectiveness analysis of treatments. When children with special health features cannot perform a self-assessment, it is possible to assess their HRQoL through their parents or caregivers. To date, the discrepancy in the assessment of HRQoL using the EQ-5D-Y questionnaire among children with cerebral palsy (CP) and their parents has not been analyzed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…In addition, there may be some discrepancies between children’s self-report and proxy reports e.g. by parents [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there may be some discrepancies between children’s self-report and proxy reports e.g. by parents [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Six studies that reported the ICCs for EQ VAS scores were excluded as there is some debate in the literature about VAS scores and the extent to which they can be interpreted as utilities [46,47,[51][52][53][54]. Kappa statistics for the domainlevel agreement were reported for 10 studies employing HUI2 and 3 (five studies) [34,[36][37][38][39]41] and EQ-5D-Y (five studies) [35,40,46,47,51]. However, since four of five studies using EQ-5D-Y did not report the standard errors of the kappa values or the percentage agreement values, the EQ-5D measure was excluded from the domain-level metaanalysis of agreement.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…The age range for children in the included studies was between 5 and 18 years. Eight studies reported children younger than 8 years of age completing a self-report questionnaire either independently or with some assistance [ 35 37 , 40 , 42 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations